Ensuring sustainability of an integrated anemia prevention and control program through social marketing - Talavera, M. T. M.; Narciso, M. H.; Tuazon, M. A. G.; Torres, C. (2003)
The study aimed to identify current knowledge, attitudes and practices (KAP) on anemia of program beneficiaries and service providers in Eastern Samar and Isabela that were used to identify entry-points for the social marketing of the integrated anemia prevention and control plans. It also lays down the social marketing mix developed given the provinces' anemia situation and KAPs. Knowledge on anemia, its causes, consequences, and intervention for its prevention and control were found inadequate in the two groups. Prevailing anemia-related attitudes and practices contributed to the serious anemia situation. Specific problems identified included: a) perception of anemia as non-life threatening disease; b) poor compliance to iron supplementation and supplementary feeding; c) negative impressions/poor understanding of programs; d) perceived non-sustainability and lack of effectiveness of programs; e) no sense of ownership of national programs; f) problematic values among beneficiaries; and g) lack of support for programs. Responding to these issues, using the 5 Ps of social marketing, the following mix of strategies were recommended: 1) Products - iron supplements, iron fortified foods (i.e., rice, bread, processed foods) should be affordable, safe, and of acceptable taste; 2) Price - products are preferred free of charge by the target groups; 3) Place - the barangay (village) health centers, botika ng bayan (town pharmacy) and sari-sari store (local/smaller versions of mom and pop stores) were mentioned best for distributing anemia commodities; 4) Promotion - this should be through mass media with products endorsed by popular but credible celebrities; and 5) Politics - local chief executives to effect political will that hopefully will address anemia and support the integrated plan.
Keywords: Anemia; Health programs